1994
DOI: 10.1073/pnas.91.20.9569
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a regulatory protein involved in the increased activity of system A for neutral amino acid transport in osmotically stressed mammalian cells.

Abstract: System A for neutral amino acid transport is Increased by hypertonic shock in NBL-1 cells previously induced to express system A activity by amino acid starvation. The hypertonicity-medated effect can be blocked by cyclobeximide but is insensitive to tuncmycin. The activity induced may be inactivated Irreversibly by the addition of system A substrates, by a rapid mehanism insensitive to cycloheximide. In CHO-Ki cells, hypertonicity increases system A activity, as has been shown in NBL-1 cells. This effect is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 37 publications
(45 reference statements)
3
31
0
Order By: Relevance
“…Taken together, these data suggest that the insulin-stimulated system A transport in adipocytes is mediated by a mechanism different from that reported in hepatocytes (15)(16)(17). The lack of repressor-type control has been reported for regulation of system A transport by other factors such as osmotic stress (5,34).…”
Section: Discussionmentioning
confidence: 37%
“…Taken together, these data suggest that the insulin-stimulated system A transport in adipocytes is mediated by a mechanism different from that reported in hepatocytes (15)(16)(17). The lack of repressor-type control has been reported for regulation of system A transport by other factors such as osmotic stress (5,34).…”
Section: Discussionmentioning
confidence: 37%
“…Three isoforms of system A have been identified: sodium coupled neutral amino acid transporter (SNAT) 1 [3], SNAT2 [4,5], and SNAT4 [6]. Amino acid uptake by system A is highly regulated in many cell types by effectors such as pH, cell volume [7] and a variety of hormones such as insulin [8], glucagon [9] and cortisol [10]. In vitro studies have demonstrated that acute incubation of primary human placental trophoblast cells and the BeWo Choriocarcinoma cell line with exogenous insulin-like growth factor-1 (IGF-1) protein increased the uptake of small neutral amino acids via amino acid transport system A [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…It is regulated by many effectors, including insulin (19), glucagon (37), cell volume (26), pH, and oxygen levels (21).…”
mentioning
confidence: 99%